(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Soil stabilization is major problem for construction and experimental purposes. Now a days used practical work greatly explains the suitable characters of the locally available Rice Husk Ash (RHA) to be used in the local construction industry in a way to minimize the amount of waste Released in environment causing issues to nature to the environment causing environmental pollution. The soil stabilization methods used in present are very costly because of costly available stabilizing materials like, cement, lime, etc. The cost of stabilization may be minimized by replacing a good proportion of stabilizing agent using RHA. It will minimize the environmental hazards also. Soil sample taken for the study is clay with high plasticity (CH) that requires stabilization. The soil is stabilized using additives rice husk ash and a small amount of coir fibre. Various results are made that shows changes in Maximum dry density (MDD), Optimum moisture content (OMC). California bearing ratio (CBR) and Unconfined compressive stress (UCS). The results obtained in the present study show that the increase in RHA content increases the OMC but decreases the MDD. Also, the CBR value and UCS of soil are considerably improved with the RHA content. From the observation of maximum improvement in strength, 10% RHA content with 6% coir fibre is recommended as optimum amount for practical purposes.